PEMASARAN JASA PADA BANK SYARIAH - Himyar Pasrizal (JURIS (Jurnal Ilmiah Syariah), 2018)
SPS-BI May 2010 period points out that Sharia banking service marketing has developed very rapidly. It is noted that there are ten Sharia banks operating throughout Indonesia. Principles of marketing – profit sharing- as applied by these banks is suitable with principles of Islamic teaching since there are no interests as practiced by conventional banks.  Furthermore, Sharia banking service offers should be based on the customer’s needs. Consequently, Sharia banking management should learn and understand how the customers behave toward the bank itself. This means that particular strategies are needed in promoting the products and factors influencing the customer’s consideration in choosing the bank. Good ”service delivery system” should meet the following indicators: available, convenient and attractive. Some strategies are also needed for the marketing: segmenting, targeting, dan positioning